2014
DOI: 10.1111/ijd.12435
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transforming growth factor‐β after different non‐invasive facial rejuvenation modalities

Abstract: Radiofrequency, ELOS, and Nd:YAG 1320-nm laser and Er:YAG 2940-nm laser mini-peels resulted in an increase in TGF-β expression, which may mediate the effects of these modalities in enhancing dermal collagen expression through the activation of fibroblasts and thereby reverse the photoaging of skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…These increases trigger TGF-β, to promote the expression of type I and XV collagen and chondroitin 6-sulfate, thus promoting fiber formation. TGF-β is reported to be increased with Nd:YAG 1320 nm and Er:YAG 2940 nm mini-peel treatments but is not increased with intense pulsed light or mesotherapy treatment [17]. A cream containing TGF-β and ascorbic acid improves the appearance of wrinkles [18].…”
Section: Discussionmentioning
confidence: 99%
“…These increases trigger TGF-β, to promote the expression of type I and XV collagen and chondroitin 6-sulfate, thus promoting fiber formation. TGF-β is reported to be increased with Nd:YAG 1320 nm and Er:YAG 2940 nm mini-peel treatments but is not increased with intense pulsed light or mesotherapy treatment [17]. A cream containing TGF-β and ascorbic acid improves the appearance of wrinkles [18].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is the master regulator of the ECM. It is known to stimulate the fibroblasts in the dermis to synthesize several proteins such as collagen, the main constituent of dermal ECM [22]. Among the most prominent are collagen type I (80-85%) and type III (10-15%), which provide strength and resilience to the skin [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the aging process affects TGF-β levels and activity. TGF-β has been shown to be lower both in in vitro aged fibroblasts, and in vivo aged skin [22,27], as well as in chronological skin aging and even more so in photo-aging. Thus, there is a need to restore the missing activity in aged skin conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of TGF-β1 was epidermal and limited to the upper differentiated layers of the epidermis [30]. However, another study by El-Domyati showed no significant differences (p ﹤ 0.05) in TGF-β1 protein expression levels among the IPL-treated and the control groups (baseline [before treatment]; end of treatment [after 3 months]; posttreatment [6 months after the start of treatment]) [31], which did not concord with Ali's study. This may be due to the different time points to obtain skin biopsies (the former detected the TGF-β1 7 days after IPL irradiation, whereas the latter obtained the biopsies 3 and 6 months after IPL irradiation) and different IPL devices and parameters.…”
Section: In Vivo Effects Of Ipl On the Skinmentioning
confidence: 97%